2013
DOI: 10.1021/ja309289u
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine Substituents Reduce Charge Recombination and Drive Structure and Morphology Development in Polymer Solar Cells

Abstract: Three structurally identical polymers, except for the number of fluorine substitutions (0, 1, or 2) on the repeat unit (BnDT-DTBT), are investigated in detail, to further understand the impact of these fluorine atoms on open circuit voltage (V(oc)), short circuit current (J(sc)), and fill factor (FF) of related solar cells. While the enhanced V(oc) can be ascribed to a lower HOMO level of the polymer by adding more fluorine substituents, the improvement in J(sc) and FF are likely due to suppressed charge recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
464
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 537 publications
(498 citation statements)
references
References 57 publications
23
464
0
Order By: Relevance
“…An auxochromic effect of the fluorine atom has also been observed by these authors, with a significantly enhanced extinction coefficient in solution and in solid state when the fluorine atom density along the conjugated backbone is increased. A similar effect has been previously observed by You and coworkers [59].…”
Section: Influence Of Fluorination On the Frontier Molecular Orbitalssupporting
confidence: 90%
See 2 more Smart Citations
“…An auxochromic effect of the fluorine atom has also been observed by these authors, with a significantly enhanced extinction coefficient in solution and in solid state when the fluorine atom density along the conjugated backbone is increased. A similar effect has been previously observed by You and coworkers [59].…”
Section: Influence Of Fluorination On the Frontier Molecular Orbitalssupporting
confidence: 90%
“…A number of recent reports have shown that fluorination of conjugated polymer backbones can have a strong impact on one or several of these properties, often leading to a more favorable morphology and to improved photovoltaic performances. Adding fluorine heteroatoms has, for instance, been found to enhance the domain purity (lowering the charge carrier recombination rate) [25,59,67], reduce the domain size [28,32,59,67], enhance the structural order [24,25,28,29,59,61,[69][70][71] and promote polymer face-on orientation at the interface with the bottom electrode [28,32,59,61,67,69,72] (increasing the out-of-plane hole mobility) or induce a face-on orientation at the D/A interface [69,73]. However, these effects can be more or less pronounced or even reversed [27,33,67], depending on the molecular structure of the conjugated building blocks as well as on the nature and positioning of the solubilizing side-chains.…”
Section: Impact Of Fluorination On the Active Layer Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…[84][85][86] Fluorination has been carried out on a wide variety of building blocks used in the synthesis of polymers, including thiophenes, carbazoles, thienothiophenes, benzothiadiazoles, benzotriazoles, benzodithiophenes, indacenodithiophenes, and anthradithiophenes. [87][88][89][90][91][92][93][94][95][96] Recently, we have shown The idea of attaching bulky substituents has also been widely used to control the packing of small molecules. [101][102][103] In particular, attaching bulky triisopropylsilyl (TIPS) groups via ethynyl linkers to the periphery of pentacene triggers the herringbone packing configuration of pentacene to transform into a 2D-brickwork packing arrangement.…”
Section: Halogen Substituents On the π-Conjugated Backbone Peripherymentioning
confidence: 99%
“…[4][5][6][7] This is attributed to the conjugated electronic and polymeric structures of these polymers, resulting in semiconducting properties with good solution processability, mechanical property and thermal stability. 8,9 Among the conjugated polymers, conjugated alternating polymers consisting of both electron donors (D) and electron acceptors (A), referred to as conjugated D-A polymers, [10][11][12][13][14][15][16][17] have been extensively investigated in recent years. The studies indicate that electronic absorptions, highest occupied molecular orbital/lowest unoccupied molecular orbital (HOMO/LUMO) energies (and bandgaps), interchain interactions and thin-film morphologies of conjugated D-A polymers can be effectively tuned [10][11][12][13][14][15][16][17] by properly varying the electron donors and acceptors as well as the linkers.…”
mentioning
confidence: 99%